Evaluation and Analysis Model of the Length of Added Displaced Left-Turn Lane Based on Entropy Evaluation Method. (12th October 2021) - Pan, Binghong; Ying, Jinfeng; Luo, Shasha; Shao, Yang; Liu, Shangru; Li, Xiang; Xie, Zhenjiang
Abstract : As the number of vehicles continues to grow in China, the problem of urban traffic congestion gets more serious, particularly at intersections. As a new type of unconventional intersection, the displaced left-turn (DLT) intersection has been widely recognized to improve the efficiency of intersections with heavy left-turn traffic flows. Converting an existing intersection into an intersection with additional DLT lanes is a valuable solution. However, the studies on DLT intersections mainly focus on performance, applicability, and safety. The guidelines on the specific engineering design process mostly come from experience, and the study on the considering multifactor design method is still insufficient. Therefore, this paper proposed an evaluation and analysis model of the lengths of added DLT lanes based on the entropy evaluation method, in which VISSIM and Surrogate Safety Assessment Model (SSAM) software were adopted for simulation. A design process for the length of the added DLT lanes was proposed with this model. An urban intersection in Xi'an was taken as a case study, and the application of the model and the design process was studied in detail. After selecting four evaluation indicators, the model was applied to calculate and analyze the optimal length of the added DLT lanes under 45 different traffic volume combinations. The recommended lengths of different situations were within the range recommended in the guidebook published by Federal Highway Administration. The results of the case study proved that the model proposed in this paper was advanced, reasonable, and practical.